Interação cinza vegetal e disponibilidade hídrica no cultivo do amendoim (Arachis hypogaea) - Reis, Renata Vilalba (2022)
In the Brazilian production scenario, choosing an alternative that increases productivity through the availability of nutrients to the plant and promotes soil fertility, without harming the environment, is increasingly relevant. One of the techniques that has stood out as an alternative to meet these requirements is the addition of agroindustrial waste, such as plant ash. This residue is a potential corrective source, due to its ability to raise the pH, contributes to the retention of water in the soil and consequently the availability of this to crops during the dry season. In this context, the objective was to evaluate the interaction of plant ash and soil water availability in peanut cultivation. The experiment was conducted in a greenhouse in 5 dm-3 pots, conducted on a randomized block design, in a 5x5 factorial scheme, corresponding to five doses of wood ash (0, 8, 16, 24 and 32 g dm-3) from the burning of Eucalyptus sp. and five water availability (25; 50; 75; 100 and 125% of the pot capacity), with four replications. The beginning of the evaluations took place at 20 days after the emergence of the plants, being carried out in the following variables: plant height, number of leaves, stem diameter and chlorophyll index; and at harvest: number of pods; number of grains per pods; number of grains produced in each pot; dry mass of grains; dry mass of pods bark; dry mass of grains without husks; dry mass of shoots; root volume; root dry mass; dry mass of shoots and roots; leaf area; number and dry mass of nodules; water consumption efficiency in the use of water. The data were submitted to the normality test to verify if they followed the normal distribution, and subsequently, submitted to analysis of variance, which, when significant, submitted to regression analysis, both at 5% probability of error, with the help of the software R Studio. The doses between 12 and 22 g dm-3 of wood ash and water availability between 86 and 113% influenced the phytometric variables of peanuts. The productive variables of peanuts were influenced by doses between 16 and 24 g dm-3 of wood ash and 86 and 112% of water availability. The plant ash acted as fertilizer and soil corrective and its addition, contributed to soil consumption, and efficiency in water use.